Evaluation of Public Sector Contributions to Public-Private Partnership Projects - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
The Bank requires that any public sector contribution to a collaborative effort between the public sector and private enterprises in the transport sector be analyzed and justified in economic terms. This Note will set out the basis for making such an analysis. The general principles underlying this analysis are that: 1) public contributions to public-private partnership (PPP) projects should be justified on the basis of external benefits from the project, compared with the scenario where no public contribution is made. 2) these external benefits are benefits for the wider economy or society which will arise from the project, but which will not be appropriated by the private partner in the contract; 3) by implication, the social welfare gain must be greater than the amount of public money invested multiplied by the cost of public funds. In practice, a range of different reasons can be - and have been - put forward to explain public contributions to PPP projects, including the following: 1) to pay for positive externalities, such as decongestion or improvements in environmental quality; 2) to contribute to the cost of mitigating negative externalities, which private providers often have little incentive to take into account when designing the project; 3) to secure network improvements necessary for economic development or other planning benefits, for which users are in the short term unable to pay. These are considered one by one in Sections 2, 3, and 4.